FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP WILLINGNESS TO PAY UNTUK PERBAIKAN KUALITAS AIR SUNGAI CODE DI KOTA YOGYAKARTA - saptutyningsih, endah (Jurnal Ekonomi & Studi Pembangunan, 2007)
This paper studies socio-economic factors influencing perceptions of the people on water quality improvement of the â€œCodeâ€ River in Yogyakarta. The factors considered in this study such as gender, number of children in family, income, duration of stay, activities in the River and the level of water quality of the River. The research values the location based on contingent valuation method (CVM) yielding two types of estimates. First, it provides simple average expressing the expected willingness to pay (expected WTP) of the respondents for water quality improvement of the River. Second, it employs the ordinary least square (OLS) to estimate those factors in relation with their willingness to pay. The result shows the influence of gender and the number of children in family on their willingness to pay for water quality improvement of the River, as also found for the duration of stay and activities in the River.